2005
DOI: 10.1590/s0004-282x2005000400030
|View full text |Cite
|
Sign up to set email alerts
|

The history of spinal surgery for disc disease: an illustrated timeline

Abstract: This article presents the evolution in medical history which leads to the surgical treatment for ruptured discs. Only at the last century the precise diagnosis of a ruptured lumbar disc could be made after tremendous efforts of the many medical pioneers in the study of the spine. The experience gained with the lumbar spine was rapidly transferred to the cervical spine. We describe the evolution of the clinical and surgical aspects about ruptured discs in the lumbar and cervical spine. An illustrative timeline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 22 publications
0
11
0
10
Order By: Relevance
“…Andreas Vesalius (1514-1564 AD) described the spinal column and intervertebral disc and Giovanni Morgagni (1682-1771 AD) reported that pressure on the spinal cord can cause paralysis of the lower extremities. 4 …”
Section: Renaissance Of Medicine In Europementioning
confidence: 99%
See 2 more Smart Citations
“…Andreas Vesalius (1514-1564 AD) described the spinal column and intervertebral disc and Giovanni Morgagni (1682-1771 AD) reported that pressure on the spinal cord can cause paralysis of the lower extremities. 4 …”
Section: Renaissance Of Medicine In Europementioning
confidence: 99%
“…Rudolf Virchow (1821-1902) described a traumatic rupture of an intervertebral disc. 4 In 1909 Alfred Taylor was the first to use a unilateral laminectomy, and Fedor Krause successfully removed a lumbar hernia. 4 Between 1927 and 1931 Schmorl, a German pathologist, established the modern basis for understanding of the intervertebral disc.…”
Section: Modern History: From Lumbar To Cervical Spinementioning
confidence: 99%
See 1 more Smart Citation
“…SCI research had its genesis in Roman times, with Galen's pioneering experiments into spinal cord levels. 5,8 However, it was not until the time of the Byzantine Empire that surgical intervention for the condition was introduced, with Paul of Aegina first performing surgical decompression in the 7th Century Common Era (CE). 2,4,6,9 He also introduced a forerunner to spinal fixation in the form of splinting.…”
Section: Introductionmentioning
confidence: 99%
“…controversial. 1 There is no clear single explanation as to why disc rupture causes back and/or radicular pain. Indeed, physical pressure on a peripheral nerve root produces paresthesia but no pain.…”
mentioning
confidence: 99%